2013
DOI: 10.1007/s10532-013-9621-x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation and proton exchange using natural rubber in microbial fuel cells

Abstract: Microbial fuel cells (MFCs) generate electricity from waste but to date the technology's development and scale-up has been held-up by the need to incorporate expensive materials. A costly but vital component is the ion exchange membrane (IEM) which conducts protons between the anode and cathode electrodes. The current study compares natural rubber as an alternative material to two commercially available IEMs. Initially, the material proved impermeable to protons, but gradually a working voltage was generated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…3b shows that there [5,18,19]. As previously reported [20], MFCs employing natural rubber as membrane improve over time as the material degrades, and after 6 months the CL-MFC continued to improve whilst maintaining a steady performance. Fig.…”
Section: Carbon Veil Vs Conductive Latex Cathodessupporting
confidence: 68%
“…3b shows that there [5,18,19]. As previously reported [20], MFCs employing natural rubber as membrane improve over time as the material degrades, and after 6 months the CL-MFC continued to improve whilst maintaining a steady performance. Fig.…”
Section: Carbon Veil Vs Conductive Latex Cathodessupporting
confidence: 68%
“…Due to the material's high cost, the majority of the work has then focused on finding alternatives that include trials with a range of materials such as j-cloth, nylon fibers, glass fibers, ceramics and biodegradable shopping bags [422], [423], [424], [425], [426], [427]. More unconventional materials, normally considered as waste such as natural rubber or laboratory gloves [428], have also been investigated [429], [430], and these materials appear to also offer advantages over membrane fouling [431]. Recently, it has also been demonstrated that a single finger piece from a laboratory glove, successfully operated a power management system, thus exhibiting practical implementation potential [249].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, less conventional, biodegradable materials have been successfully applied. Natural rubber has proven to be a viable substitute to conventional membranes over long term operation where the act of biodegradation actually aided performance [22]. Other materials such as paper [16], egg, gelatine, PLA and lanolin have all demonstrated their suitability as viable working components in MFCs [23].…”
Section: The Power Source For Biodegradable Robotsmentioning
confidence: 99%